Wisconsin Sentencing in the Tough-on-Crime Era : How Judges Retained Power and Why Mass Incarceration Happened Anyway - O'Hear, Michael, 1968- (Book collections on Project MUSE., 2017)
The dramatic increase in U.S. prison populations since the 1970s is often blamed on the mandatory sentencing required by ""three strikes"" laws and other punitive crime bills. Michael O'Hear shows that the blame is actually not so easily assigned. His meticulous analysis of incarceration in Wisconsin-a state where judges have considerable discretion in sentencing-explores the reasons why the prison population has ballooned nearly tenfold over the past forty years. O'Hear tracks the effects of sentencing laws and politics in Wisconsin from the eve of the imprisonment boom in 1970 up to the 2010s.